2019
DOI: 10.1111/bjet.12770
|View full text |Cite
|
Sign up to set email alerts
|

Where is the “theory” within the field of educational technology research?

Abstract: Khe Foon Hew is an Associate Professor of Information Technology in Education at the University of Hong Kong. His research investigates the use of educational technology in K-12 and university settings, and computer-mediated communication with a particular focus on social media applications. Min Lan is a final year PhD candidate of Information Technology in Education at the University of Hong Kong. Min's research interests lie in the area of technology-enhanced learning, particularly in the area of online lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 51 publications
5
123
0
6
Order By: Relevance
“…It is unlikely that such strong or general AI will exist in the near future. We are therefore dealing here with GOFAI ("good old-fashioned AI", a term coined by the philosopher John Haugeland, 1985) in higher educationin the sense of agents and information systems that act as if they were intelligent.…”
Section: Ai In Education (Aied)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that such strong or general AI will exist in the near future. We are therefore dealing here with GOFAI ("good old-fashioned AI", a term coined by the philosopher John Haugeland, 1985) in higher educationin the sense of agents and information systems that act as if they were intelligent.…”
Section: Ai In Education (Aied)mentioning
confidence: 99%
“…The lack of theory might be a syndrome within the field of educational technology in general. In a recent study, Hew, Lan, Tang, Jia, and Lo (2019) found that more than 40% of articles in three top educational technology journals were wholly a-theoretical. The systematic review by Bartolomé et al (2018) also revealed this lack of explicit pedagogical perspectives in the studies analysed.…”
Section: Conclusion and Implications For Further Educational Researchmentioning
confidence: 99%
“…Hence, purely deductive approaches in distance education tend to be relatively rare and more usually include a blend of both deductive and inductive approaches (Cohen et al 2011, p. 3). Beyond these, an abductive approach is required to construct theory, or generate 'suitable hypotheses', when current theories are insufficient, such as the case of much of education technology research (Hew et al 2019). This aligns with Peirce's original form of abduction as a pragmatic activity of exploration (Peirce 1955), perhaps best encapsulated by Frankfurt's summary of it as a process to construct "the admissibility of hypotheses to rank as hypotheses."…”
Section: Approach and Methodsmentioning
confidence: 99%
“…Das TPACK-Modell von Mishra und Koehler (2006) berücksichtigt neben den drei von Shulman (1986Shulman ( , 1987 (Chai, Koh & Tsai, 2013;Hew, Lan, Tang, Jia & Lo, 2019;Voogt, Fisser, Pareja Roblin, Tondeur & van Braak, 2013;Willermark, 2018…”
Section: Das Tpack-modellunclassified